How is the correlation job crafting to job satisfaction of hospital staff at disruption era in hospital industries - Andi Indahwaty Sidin; Lalu Muhammad Saleh; Eka Fatmawati; Indah Nur Insani (Elsevier, 2021)
Objective: This study aimed to see the correlation between JC and JS of hospital staff in Rural area, Mamuju at 4.0 era. Method: The population was all staff of three hospitals, 614 respectively at Mamuju regency, West Sulawesi Province and 155 staff selected as samples. The sample was chosen by random quota sampling, then analyzed using the Spearman correlation test. Results: The results showed that most of the staff were satisfied with their job (90% average) while more than 80% of staff perceived the did JC. The result of the correlation test revealed that the p value of 0.005 < 0.05 means hypothesis null was rejected. There was correlation between JC and JS. The correlation coefficient was 0.224 showing a positive direction of the relationship even though it was a weak correlation. Conclusions: JC can cause JS when the staff have other supporting factors. JC may enhance JS significantly when supported by other factors, such as job security, good compensation work itself and relationship with immediate supervisor.